Sleep disorders mediate the link between childhood trauma and depression severity in children and adolescents with depression - Luo, Bei; Yang, Yingying; Zhang, Dapeng; Zhang, Qing; Liu, Zhichun; Wang, Song; Shi, Yudong; Xia, Lei; Wang, Jiawei; Liu, Zhiwei; Geng, Feng; Chen, Changhao; et al. (Frontiers in Psychiatry, 2022)
Abstract Background Childhood trauma is closely related to the onset of depression and more severe depressive symptoms; however, the specific mechanisms are unclear. We aimed to examine the relationship between childhood trauma and sleep disorders in children and adolescents with depression and to explore further the role of sleep disorders in the relationship between childhood trauma and depression severity. Methods Total of 285 children and adolescents with depression completed all scale assessments, including the Childhood Trauma Questionnaire, Self-Reported Insomnia Severity Index and Epworth Sleepiness Scale, and the Center for Epidemiologic Studies Depression Scale. A simple mediation model was used as a theoretical model to examine whether sleep disorders could mediate the relationship between childhood trauma and depression severity. Results Among children and adolescents with depression, childhood trauma is about 78.9%. Compared with patients without childhood trauma, patients with childhood trauma had a higher incidence of sleep disorders (Z=17.59, P<0.001), which were characterized by insomnia (Z=14.45, P<0.001), not hypersomnia (Z=2.77, P=0.096). Different childhood trauma subtypes significantly affected sleep disorders and insomnia (all P values were less than 0.05). Insomnia partially mediated the relationship between childhood trauma and depression severity, and the mediating effect accounted for 35.90%. Conclusion This study found a high rate of concurrent childhood trauma and insomnia among children and adolescents with depression. Insomnia, as a mediator between childhood trauma and depression severity, partially mediates the relationship.